A new species of the genus Meilichius Gerstaecker (Coleoptera: Endomychidae: Cyclotominae) from Guangxi, China - Wang, Cheng Bin; Tomaszewska, Wioletta (Zootaxa, 2025)
A new species of handsome fungus beetles, Meilichius wukong sp. nov., is described from Guangxi, South China. Illustrations of its habitus and diagnostic characters are provided, together with a differential diagnosis distinguishing it from the most similar M. ornatus Arrow, 1920. In addition, the lectotype of M. ornatus is designated.